Relación entre parámetros de tensiomiografía y potenciales indicadores del rendimiento en ciclistas profesionales - Garcia-Garcia, O. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2013)
The aim of this study was to establish the relationship of the time contraction (TC) and the radial muscle belly displacement (DM) of the vastus medialis, vastus lateralis, rectus femoris and biceps femoris muscles, assessed by tensiomyography, regarding potential sport performance indicators such as Wmax and VO2max in professional road cyclists. A tensiomyography and a progressively incremental protocol until exhaustion point were reached in the laboratory conditions to 10 professional cyclists. The results show that there are correlations between performance indicators and the DM of biceps femoris and rectus femoris, and between the own indicators Wmax and VO2max. However, the TC has not correlated with any of them. In conclusion, the results suggest that DM of the biceps femoris and rectus femoris biarticular muscles could be related with these potential sport performance indicators of the professional cyclists.